Development and application of hybrid nanomaterial single-site catalysts by surface modification of metal oxide nanoparticles - Dwaipayan, Ghosh (2019)
Catalyst deactivation is an intriguing issue that has created immense problems not only for the industry but also for the global scientific community. Isolated single-site heterogeneous catalysts can potentially overcome these problems. In this thesis, we have explored a simple yet reproducible anchoring strategy for immobilization of molecular complexes on a wide range of metal oxide (e.g. titanium dioxide, mesoporous silica, cerium oxide, and tungsten oxide) nanoparticles to synthesize isolated single-site catalysts. Maleimide, an oxidatively stable anchoring group, forms a covalent bond with surface hydroxyl groups present on the metal oxide surface via photoclick chemistry. The hybrid nanomaterials have been extensively characterized by several techniques including UV-visible diffuse reflectance spectroscopy (UV-DRS), high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), Fourier-transform infrared spectroscopy (FT-IR), and X-ray absorption spectroscopy (XAS). The formation of the covalent linkage was confirmed by the FT-IR spectroscopic study. The hybrid nanocomposites were found to be highly efficient for the oxidation of terminal as well as internal alkenes. The conversions of the starting materials and selectivity towards epoxide product was found to be comparable to the molecular catalyst even in environmentally benign solvents. XAS and FT-IR studies confirm the robustness of the hybrid catalyst, even after several catalytic cycles. The photoclick anchoring technique was applied to deposit a luminescent complex precisely at the desired locations on the metal oxide nanoparticles surfaces. Overall, a facile and general approach was demonstrated to anchor molecular catalysts on a wide range of metal oxide nanomaterial surfaces. This spatially and temporally controllable photoclick methodology can be appllied to other ligands, catalysts, functional molecules, and surfaces.